Critical review of the current literature on the safety of sucralose. (August 2017) - Magnuson, Bernadene A.; Roberts, Ashley; Nestmann, Earle R.
Abstract: Sucralose is a non-caloric high intensity sweetener that is approved globally for use in foods and beverages. This review provides an updated summary of the literature addressing the safety of use of sucralose. Studies reviewed include chemical characterization and stability, toxicokinetics in animals and humans, assessment of genotoxicity, and animal and human feeding studies. Endpoints evaluated include effects on growth, development, reproduction, neurotoxicity, immunotoxicity, carcinogenicity and overall health status. Human clinical studies investigated potential effects of repeated consumption in individuals with diabetes. Recent studies on the safety of sucralose focused on carcinogenic potential and the effect of sucralose on the gut microflora are reviewed. Following the discovery of sweet taste receptors in the gut and studies investigating the activation of these receptors by sucralose lead to numerous human clinical studies assessing the effect of sucralose on overall glycemic control. Estimated daily intakes of sucralose in different population subgroups, including recent studies on children with special dietary needs, consistently find that the intakes of sucralose in all members of the population remain well below the acceptable daily intake. Collectively, critical review of the extensive database of research demonstrates that sucralose is safe for its intended use as a non-caloric sugar alternative. Highlights: Comprehensive review of sucralose toxicology: growth, development, genetox, reproduction, neurotoxicity, and carcinogenicity. No adverse effect on health or glycemic indices following long-term sucralose consumption in healthy and diabetic subjects. Estimated intakes of sucralose remain well below acceptable daily intake values. Confirms conclusions of regulatory agencies globally that sucralose is safe for intended uses as a non-caloric sweetener.